SAT0399 RISK OF OSTEOARTHRITIS IN AN INCIDENT COHORT OF PEOPLE WITH PSORIATIC ARTHRITIS: A POPULATION-BASED COHORT STUDY. (2nd June 2020) - Charlton, R.; Green, A.; Shaddick, G.; Snowball, J.; Nightingale, A.; Tillett, W.; Smith, C.; Mchugh, N.; Tillett, W.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory arthritis that causes pain, stiffness and swelling around the joints. PsA is reported to affect between 10 and 40% of individuals with psoriasis 1 and in the majority of patients presents after, or synchronously with, psoriasis onset. 2 Osteoarthritis (OA) is a common form of non-inflammatory arthritis related to joint degeneration and typically commences late in the fifth decade. PsA and OA have long been considered two distinct arthropathies, however they do have some overlapping features and symptoms and in certain circumstances it can be difficult to differentiate between them, particularly in the small joints of the hands or spine. 3 Objectives: To determine the risk of a diagnosis of osteoarthritis in psoriatic arthritis patients compared to patients with psoriasis and a general population cohort. Methods: Incident PsA patients aged 18-89 years at diagnosis were identified from the UK Clinical Practice Research Datalink between 1998 and 2014. All PsA patients were matched to a cohort of patients with psoriasis and a general population cohort (with no psoriasis or PsA) at a 1:4 ratio based on index date, year of birth, sex and general practice. The baseline prevalence of OA of any site was calculated as a percentage for each study cohort and then those prevalent cases were excluded from the numerators and denominators of the incident calculations. The incidence of OA was calculated and relative risks (RRadj ), adjusting for body mass index (BMI), were calculated using conditional Poisson regression. Results: In total, 6, 783 incident PsA patients were identified. The baseline prevalence of OA ranged from 22.1% (CI95 21.1-23.1) in the PsA cohort to 12.6% (CI95 12.2-13.0) and 11.0% (CI95 10.6-11.3) in the psoriasis and general population cohorts respectively. The incidence of OA was significantly higher in the PsA cohort compared to the psoriasis and general population cohorts after adjusting for BMI (RRadj 1.68 CI95 1.46-1.93 and RRadj 1.86 CI95 1.62-2.14 respectively) (Tables 1 and 2). Conclusion: An increased risk of OA was observed in patients with PsA compared to patients with psoriasis alone and those in the general population. Further work is needed to determine whether this reflects a true increase in OA risk or misdiagnosed PsA and the extent to which it can be explained by differences in the opportunity for OA diagnosis between cohorts. References: [1]Ogdie A, Weiss P. Rheum Dis Clin North Am. 2015;41(4):545-568. [2]Tillett W et al. Rheumatol. 2017;56(12):2109-2113. [3]McGonagle D et al . Rheumatology. 2015;54(1):29-38. Acknowledgments: This report is independent research funded by the National Institute for Health Research, Programme Grants for Applied Research [Early detection to improve outcome in patients with undiagnosed PsA ('PROMPT'), RP-PG-1212-20007]. The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care. Disclosure of Interests: None declared